Membumikan Nilai-Nilai Edukasi dalam Kitab Abdul Alim Wal Mutaalim di Era Modern - Asrowi, Asrowi (E-JURNAL AKSIOMA AL-ASAS, 2024)
The value of education is one of the most important issues in contemporary society and nation-building. We no longer underestimate the importance of education. Globalization and modernization have led to a decline in the value of education. We must take action to address educational values that are invisible to students. One of the actions involves studying references regarding educational values that align with the conditions and rules of Indonesian culture. Social education encompasses a variety of activities such as fostering social relationships, fostering harmonious relationships between students and educators, interacting with scholars, and communicating moral values. Among other things, moral education and the creation system ensure that the conversation is not interrupted. Cultural education encompasses a variety of activities such as delivering praise to students, extending greetings, and adhering to the lecture order. Keywords: Educational Value, Book of Abdul Alim Wal Mutaalim, Modern Era